Pre-Exposure Prophylaxis for viral infections other than HIV - Soriano, Vicente; Treviño, Ana; de Mendoza, Carmen; Moreno-Torres, Víctor; Pintos, Ilduara; Barreiro, Pablo; Corral, Octavio Jorge (Infezioni in Medicina, 2023)
The battle against human viral infections has histori-cally relied on two medical strategies, namely vaccines to protect from contagion and antivirals to treat infected patients. In the absence of vaccines, antivirals have occasionally been used as periexposure prophylaxis, given either before (pre-exposure prophylaxis) or right after (post-exposure prophylaxis). In an unprecedented way, the use of antiretrovirals as chemoprophylaxis has triumphed in the HIV field. Indeed, oral antiretro-virals given either daily or at demand to HIV-uninfected individuals engaged in high-risk behaviors protect from contagion. More recently, the advent of long-acting formulations has allowed HIV protection following intramuscular injections every three months. Can we envision a similar prophylactic strategy for other human viral infections? The advent of such ‘chemical vaccines’ would fill an unmet need when classical vaccines do not exist, can-not be recommended, immune responses are suboptimal, escape mutants emerge or immunity wanes. In this review, we discuss the opportunities for antiviral chemoprophylaxis for viral hepatitis B and C, retroviruses HTLV-1 and HIV-2, and respiratory viruses influenza and SARS-CoV-2, among others.
Keywords: antiviral drugs; hepatitis B; hepatitis C; HIV; HTLV-1; long-acting antivirals; mon-keypox virus; prevention; prophylaxis; SARS-CoV-2; Scopus